Overview Of Personal Hygiene During Menstruation In Kesuma Indah High School Padangsidimpuan In 2021 - Rini Yolanda Sitorus (Sean Institute, 2023)
During menstruation, which last for several days, women must maintain personal hygiene. Menstrual personal hygiene is a woman’s personal hygiene duting menstruation which aims to prevent disease and increase feelings of well-being. While menstruating, the cleanliness of the reproductive organs is very important to maintain and pay attention to cleanliness in order to avoid reproductive health problems. The method used in this study is a quantitative method. The result showed as many as 51 people (53.1%) with sufficient result in performing personal hygiene during menstruation in children of SMA Kesuma Indah Padangsidimpuan. Respondents are expected to be able to improve personal hygiene during menstruation so as ato avoid problems in reproductive health. Then it was concluded that personal hygiene during menstruation in Kesuma Indah High School children still had to be improved so that they were better in personal hygiene behavior during menstruation.